Enabling Intrapreneurship : A Case of A Chinese Family Business and SMEs in Malaysia - Chia, Woan Tyng (2011)
The objective of this study is to conduct an exploratory study into the intrapreneurial behavior in southeast Chinese family business firms. This is very much in response to the fact that current available literatures in corporate entrepreneurship are mainly focused on western well-established organizations. Whereas, the study of corporate entrepreneurship in Chinese family business context are still lacking.This study target discloses whether the enablers of corporate entrepreneurship, which were found consistent on current literature, would contribute in intrapreneurial behavior in a Chinese family firm.Data in this study were collected and analyzed by face-to-face interviews with the employees in a Chinese family business firm in Malaysia. All the respondents were a cross section of senior managers in the firm.The finding shows that intrapreneurial behavior is just as vital in a Chinese family business.It is however, the factors that could stimulate employees innovative behavior do not goes along with the literature. It is notable that the simplicity structure of the firm, centralization decision-making process and the adoption of early professionalize strategy could surprisingly stimulate intrapreneurial behavior within a Chinese family business firm.